Halloysite nanotubes: Natural, environmental-friendly and low-cost nanomaterials for high-performance humidity sensor - Duan, Zaihua; Zhao, Qiuni; Wang, Si; Huang, Qi; Yuan, Zhen; Zhang, Yajie; Jiang, Yadong; Tai, Huiling (Sensors and actuators. B, Chemical, 2020)
[Display omitted] •The humidity sensor based on halloysite nanotubes (HNTs) is firstly fabricated.•The HNTs humidity sensor has a large response of five orders of magnitude.•The response time of the HNTs humidity senor is only about 0.7 s.•The HNTs humidity senor has wide humidity detection range of 0–91.5% RH.•The HNTs humidity senor has an obvious response to very low RH of 7.2%. Benefiting from the development of nanomaterials synthesis technology, the performance of many electronic devices, including humidity sensors, has been improved greatly. However, the synthesis of nanomaterials usually involves complex processes, expensive raw materials and even toxic reagents. Herein, the natural nanomaterials of halloysite nanotubes (HNTs) are deliberately selected for the fabrication of high-performance humidity sensor. Characterization results show that the HNTs have good hydrophilicity, hollow tubular nanostructure and large specific surface area, which contribute to humidity sensing performance of the humidity sensor. Further, the humidity sensor based on HNTs is fabricated and its humidity sensing properties are tested at the room temperature (25 °C). The results show that the impedance variation of the HNTs humidity sensor is five orders of magnitude within the humidity range from 0% to 91.5% relative humidity (RH) at the optimum working frequency (100 Hz), and its response time is only about 0.7 s. Notably, the HNTs humidity sensor exhibits wide humidity detection range of 0–91.5% RH, very low RH (7.2%) response characteristic and good linear responses at 0–28.8% and 28.8–91.5% RH. This work provides a simple, low-cost and environmental-friendly strategy for fabricating high-performance humidity sensor by exploring the natural nanomaterials like HNTs.